Avant-garde Pedagogical Practise Utilizing Virtual Environments and Machinima in Systems Development - Dreher, Naomi; Dreher, Heinz (International Journal of Emerging Technologies in Learning (iJET), 2010)
Inspired by the success of the Students @ Work project [1] run at Hamburg University, Curtin University (Perth, Western Australia) has recently concluded the running of a pilot course in Second Life with their Information Systems Project (ISP) students. The need for a change was evident as student motivation and engagement in the Final Year ISP course was strikingly low. Left with such a tall order for improvement, the ISP teaching staff looked to find suitable options for change. Staff combined new and interesting tools in an effort to boost and maintain student interest, specifically the Second Life virtual environment and a screen capturing technique known as Machinima.